Risk-Based Regulatory Model for Healthcare Workers with Communicable Diseases in Ensuring Patient Safety in Indonesia - Anak Agung Gede Jaya Semara; I Nyoman Bayu Mahendra (Griya Eka Sejahtera, 2026)
Background: Patient safety is a fundamental principle in healthcare systems aimed at ensuring safe and high-quality healthcare services. However, Indonesian regulations concerning healthcare workers with communicable diseases remain inadequate, particularly regarding periodic health screening and risk-based practice restrictions. This study aimed to analyze the Indonesian legal framework from a patient safety perspective and to formulate a risk-based regulatory model. Methods: This study employed normative legal research using statutory, conceptual, and comparative approaches. The statutory approach examined Indonesian laws and regulations related to patient safety, healthcare workers, infection prevention and control, and labor law. The conceptual approach analyzed principles of health law and bioethics, including patient safety, non-maleficence, beneficence, and the precautionary principle. The comparative approach compared Indonesian regulations with international standards issued by the Centers for Disease Control and Prevention (CDC) and the National Health Service (NHS). Data were collected through documentary and library research using primary, secondary, and tertiary legal materials. Data analysis was conducted qualitatively through grammatical interpretation, systematic interpretation, and legal harmonization analysis. Results: The study found that Indonesian regulations have not comprehensively regulated periodic health screening, risk-based practice restrictions, and monitoring systems for healthcare workers with communicable diseases. Significant normative gaps and legal uncertainty remain regarding the balance between healthcare workers’ rights and patient safety. Compared with CDC and NHS standards, Indonesia has not yet optimally implemented a risk-based regulatory approach. Conclusion: Indonesia requires a comprehensive risk-based health regulatory framework integrating patient safety, healthcare workers’ rights, and proportional supervisory mechanisms. The proposed “Risk-Based Integrated Health Regulation” model may serve as a foundation for future health law reform and patient safety protection in Indonesia.